Configuration-dispatch dual-layer optimization of multi-microgrid–integrated energy systems considering energy storage and demand response - Wang, Kaiyan; Liang, Yan; Jia, Rong; Wang, Xueyan; Du, Haodong; Ma, Xiping (Frontiers in Energy Research, 2022)
With the urgent demand for energy revolution and consumption under China’s “30–60” dual carbon target, a configuration-scheduling dual-layer optimization model considering energy storage and demand response for the multi-microgrid–integrated energy system is proposed to improve new energy consumption and reduce carbon emissions. First, a demand response model of different users and loads in the integrated energy system is established. Second, the upper energy storage configuration model is constructed by introducing shared energy storage in the multi-microgrid–integrated energy system to improve the system’s flexibility, with the optimization goal of the maximum annual profitability of shared energy storage. A carbon trading mechanism considering the dynamic reward coefficient is designed. A low-carbon economic dispatch model of a multi-microgrid–integrated energy system is constructed based on the upper energy storage capacity, charge and discharge power, and user-side demand response with the lowest annual operating cost as the optimization goal. Finally, the effectiveness of the proposed model is verified by case studies in various scenarios. The results illustrate that the proposed model can fully use demand-side controllable resources to improve system energy utilization, effectively reduce carbon emissions, and further improve the operation economy of the multi-microgrid–integrated energy system.